CompTIA Security+ (SY0-601) Cert Prep: 6 Cloud Security Design and Implementation. - Chapple, Mike (linkedin.com, 2020)
Explore the world of cloud security as you study for version SY0-601 of the CompTIA Security+ exam. Learn about virtualization, essential cloud computing concepts, and more.